2018
DOI: 10.1186/s12863-017-0591-6
|View full text |Cite
|
Sign up to set email alerts
|

Association between sequence variants in panicle development genes and the number of spikelets per panicle in rice

Abstract: BackgroundBalancing panicle-related traits such as panicle length and the numbers of primary and secondary branches per panicle, is key to improving the number of spikelets per panicle in rice. Identifying genetic information contributes to a broader understanding of the roles of gene and provides candidate alleles for use as DNA markers. Discovering relations between panicle-related traits and sequence variants allows opportunity for molecular application in rice breeding to improve the number of spikelets pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…Alternatively sequence variations might occur at very low frequency and thus not be observed or filtered out in our analysis. Nevertheless a recent analysis revealed that a combination of favourable alleles for these genes might collectively produce a higher spikelet number in a specific panel, supporting the notion that there is a complex genetic network regulating this phenotypic feature [ 58 ].…”
Section: Discussionmentioning
confidence: 93%
“…Alternatively sequence variations might occur at very low frequency and thus not be observed or filtered out in our analysis. Nevertheless a recent analysis revealed that a combination of favourable alleles for these genes might collectively produce a higher spikelet number in a specific panel, supporting the notion that there is a complex genetic network regulating this phenotypic feature [ 58 ].…”
Section: Discussionmentioning
confidence: 93%
“…Contrastingly, H4 haplotype showed inclination towards dense branching trait. One recent study has shown the association of gene SHORT PANICLE 1 (SP1) and elevated haplotype diversity among japonica than indica group (Jang et al, 2018).…”
Section: Linkage Disequilibrium and Haplotype Analysismentioning
confidence: 99%
“…Rice panicle length (PL), as a yield‐related trait determined by the rachis length plus primary branch length above the rachis tip, is a key agronomic characteristic that varies widely amongst cultivars (Ikeda, Sunohara, & Nagato, ). This trait strongly impacts grain yield by affecting several panicle‐related traits, such as the number of primary branches per panicle, the number of secondary branches per panicle and the grain density per panicle (Jang et al, ; Peng et al, ). Elite indica rice cultivars with high yield have more spikelets than japonica cultivars because of the longer panicle and they are under different genetic control as revealed by genome‐wide association analysis (Bai et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the interaction of genotype by genotype (G × G) and genotype by environment (G × E) contributed to the trait variation (Cho et al, ; Hittalmani et al, ; Zhang et al, ). Correlation analysis also revealed the strong relationship between PL and other agronomic traits, including panicle culm length, plant height, heading stage, secondary branch number and spikelet number per panicle, and these correlated traits are usually mapped synchronously (Dang et al, ; Guo & Hong, ; Huang et al, ; Jang et al, ; Liang, Shang, Lin, Lou, & Zhang, ; Lu et al, ; Miura et al, ; Sun et al, ; Wu et al, ; Yan et al, ; Zhang, Luo, Xu, Zhang, & Xing, ), Genetic dissection for rice plant architecture showed that the PL QTL is co‐localised with either culm length, tiller number or both (Kobayashi et al, ) and finely mapped with the same locus for spikelet number per panicle (Guo & Hong, ; Xie et al, ). However, whether the loci are in tight linkage or genes are in pleiotropy is unclear.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation